Perceptions of equity in conservation scenarios: Half Earth and Sharing the Planet. Issue 144 (June 2023) - de Bruin, Sophie P.; van Vliet, Jasper; Lehmann, Ina; Verburg, Peter
Abstract: The Half Earth (HE) and Sharing the Planet (SP) scenario narratives are two distinctly different scenarios on how to restore and conserve biodiversity while accounting for the need for agricultural production. Yet, the equity implications of both scenarios are not clear. We conducted a questionnaire to better understand what experts with various backgrounds perceive as the main equity implications of these scenarios. We find that, overall, distributive, recognitional, and procedural equity barriers are perceived as higher in the HE scenario, as is the possibility of reaching equity. Especially people depending on local biodiversity to sustain their livelihoods are perceived to face challenges due to inequities. Although equity risks are perceived to be lower in the SP scenario, the measures needed to achieve this scenario are seen as hard to implement, since existing economic and political power structures need to change. Some respondents perceive the SP scenario as anthropocentric, and therefore not equitable to non-humans. The equity perceptions are linked to the respondents' attitudes to nature, their professional focus, and their view on equity in nature conservation and agriculture discussions and agreements today. These results indicate that it is important to recognise the different equity implications of the different scenarios and the challenge to provide equity implications for such scenarios. Explicitly recognising different equity understandings in scenario development and science-policy interfaces could lead to more inclusive policies. Highlights: Addressing equity is essential in working towards a sustainable future. Equity in the Half Earth and Sharing the Planet narrative is perceived differently. Perceptions of equity risks and barriers are larger in the Half Earth narrative. Making equity implications explicit add to the credibility of scenarios. Discussing equity implications make scenarios better connected to policy realities.